Intracortical Inhibition and Surround Inhibition in the Motor Cortex: A TMS-EEG Study - Leodori, Giorgio; Thirugnanasambandam, Nivethida; Conn, Hannah; Popa, Traian; Berardelli, Alfredo; Hallett, Mark (Frontiers in Neuroscience, 2019)
Background: Short-latency intracortical inhibition (SICI) and motor surround inhibition (mSI) are cortical phenomena that have been investigated with Transcranial Magnetic Stimulation (TMS). mSI is believed to be necessary for the execution of fine finger movements, and SICI may participate in mSI genesis, however, the mechanisms underlying both mSI and SICI are not entirely clear. Objective: We explored the cortical physiology of SICI and mSI in healthy subjects by TMS-evoked cortical potentials (TEPs). Methods: Single (sp) and paired-pulse (pp) TMS were delivered on the ADM muscle cortical hotspot while recording EEG and EMG. Three conditions were tested: spTMS and ppTMS at rest, and spTMS at the onset of an index finger movement. SICI and mSI were calculated on the ADM motor evoked potential (MEP) and two groups were defined based on the presence of mSI. Average TEPs were calculated for each condition and for five regions of interest. Results: At movement onset we observed a widespread reduction of the inhibitory late component N100 suggesting cortical facilitation associated with motor performance. At motor cortex level, SICI and mSI are associated with similar modulation of TEPs consisting in a reduction of P30 and an increase of N45 amplitude. Conclusions: Our findings suggest that SICI and mSI modulate cortical excitability with shared inhibitory mechanisms.